2017
DOI: 10.1371/journal.pone.0171006
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dementia from proton pump inhibitor use in Asian population: A nationwide cohort study in Taiwan

Abstract: IntroductionConcerns have been raised regarding the potential association between proton pump inhibitor (PPI) use and dementia.ObjectiveThis study aimed to examine this association in an Asian population.MethodsPatients initiating PPI therapy between January 1, 2000 and December 31, 2003 without a prior history of dementia were identified from Taiwan’s National Health Insurance Research Database. The outcome of interest was all-cause dementia. Cox regression models were applied to estimate the hazard ratio (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 40 publications
6
88
3
7
Order By: Relevance
“…Using time‐varying methods, both studies examined risk of dementia over the 18 months after ascertainment of PPI use. Lastly, PPI use was associated with greater dementia risk (HR = 1.22, 95% CI = 1.05–1.42) in a cohort study using administrative data from the Taiwan National Insurance Research Database …”
Section: Discussionmentioning
confidence: 97%
“…Using time‐varying methods, both studies examined risk of dementia over the 18 months after ascertainment of PPI use. Lastly, PPI use was associated with greater dementia risk (HR = 1.22, 95% CI = 1.05–1.42) in a cohort study using administrative data from the Taiwan National Insurance Research Database …”
Section: Discussionmentioning
confidence: 97%
“…However, this study was at risk of misclassification bias due to self‐reporting of PPI use and missing data. A retrospective cohort study of 15,726 patients in Taiwan found that PPI use increased the risk of developing dementia compared to non‐use . These authors also reported that the risk of developing dementia increased with higher doses of PPIs.…”
Section: Resultsmentioning
confidence: 98%
“…Regarding the dementia risk, initially, three cohort studies (Gomm et al, ; Haenisch et al, ; Tai et al, ) and one cross‐sectional study (Herghelegiu, Prada, & Nacu, ) found a positive association between dementia risk and PPI use. However, this association was not found in more recent studies, including a case control study (Imfeld, Bodmer, Jick, & Meier, ) and a cohort study (Gray et al, ).…”
Section: Resultsmentioning
confidence: 99%